SSU1 Checkup, a Rapid Tool for Detecting Chromosomal Rearrangements Related to the SSU1 Promoter in Saccharomyces cerevisiae: An Ecological and Technological Study on Wine Yeast - Marullo, Philippe; Claisse, Olivier; Raymond Eder, Maria Laura; Börlin, Marine; Feghali, Nadine; Bernard, Margaux; Legras, Jean-Luc; Albertin, Warren; Rosa, Alberto Luis; Masneuf-Pomarede, Isabelle (Frontiers in Microbiology, 2020)
Chromosomal rearrangements (CR) such as translocations, duplications and inversions play a decisive role in the adaptation of microorganisms to specific environments. In enological Saccharomyces cerevisiae strains, CR involving the promoter region of the gene SSU1 lead to a higher sulfite tolerance by enhancing the SO2 efflux. To date, three different SSU1 associated CR events have been described, including translocations XV-t-XVI and VIII-t-XVI and inversion inv-XVI. In the present study, we developed a multiplex PCR method (SSU1 checkup) that allows a rapid characterization of these three chromosomal configurations in a single experiment. Nearly 600 S. cerevisiae strains collected from fermented grape juice were genotyped by microsatellite markers. We demonstrated that alleles of the SSU1 promoter are differently distributed according to the wine environment (cellar versus vineyard) and the nature of the grape juice. Moreover, rearranged SSU1 promoters are significantly enriched among commercial starters. In addition, the analysis of nearly isogenic strains collected in wine related environments demonstrated that the inheritance of these CR shapes the genetic diversity of clonal populations. Finally, the link between the nature of SSU1 promoter and the tolerance to sulfite was statistically validated in natural grape juice containing various SO2 concentrations. The SSU1 checkup is therefore a convenient new tool for addressing population genetics questions and for selecting yeast strains by using molecular markers.